Students, Entrepreneurship and Empowerment: A Case Study Humane Entrepreneurship Strategy at Bahrul Maghfiroh Islamic Boarding School, Malang City - Sopiyatun; A. Muhtadi Ridwan; Aunur Rofiq (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study explores the intersection of students, entrepreneurship, and empowerment through a case study of the humane entrepreneurship strategy implemented at Bahrul Maghfiroh Islamic Boarding School in Malang City. In response to the increasing need for economic independence and the cultivation of entrepreneurial spirit among students, Bahrul Maghfiroh has developed a unique approach that integrates ethical business practices with educational goals. This research employs a qualitative case study method, gathering data through interviews, observations, and documentation analysis. Findings reveal that the boarding school adopts a humane entrepreneurship model characterized by prioritizing student welfare, ethical management, and community engagement, while fostering practical entrepreneurial skills. Through various business units and training programs, students are not only educated in Islamic knowledge but are also equipped with real-world business competencies, contributing to their personal development and future economic resilience. This study highlights how humane entrepreneurship can serve as a powerful tool for student empowerment in Islamic educational institutions, offering a sustainable model for other boarding schools seeking to combine education, character-building, and economic independence.